The development of an analyses-intensive software for improved cams systems design (2008)
The computer-aided software developed in this research work is used in designing cam systems by generating various follower motions and cam profiles. It is highly suited for extensive dynamics, kinematics and geometric design analysis based on some inherent features that are unique. The plate cam with either flat-face or roller followers can be designed. Most of the standard and acceptable cam functions are included such as double harmonic, modified trapezoidal, cycloid, 4-5-6 polynomial and others. Various prime circle radii and follower face widths are calculated for flat-face follower design option for any user selected cam angle, follower profile and cam function. Other parameters such as minimum and maximum values of radii of curvature, pressure angle, are also calculated for roller follower design option. In every design the follower motion and cam profiles are calculated and coordinate files can be exported in Cartesian format and automatically imported into a spreadsheet package thereby using all its features for better analysis of results. All dynamic, kinematics and geometric parameters can be plotted and all data may be printed to the screen, to a printer, or to a file.